PRINSIP-PRINSIP PENGGUNAAN BAHASA SEBAGAI ALAT KOMUNIKASI INTERAKTIF DAN MENJALIN HUBUNGAN BAIK - Naffa Asti Aprilia; Agiska Cahnia; Noviyanti, Silvina (Jurusan Pendidikan Luar Biasa, 2024)
Communication plays an important role in inclusive education, where the use of polite, inclusive, and clear language helps build strong relationships between teachers, students, parents, and support staff. This research aims to analyze the principles of language use as an interactive communication tool and to build good relationships in the context of inclusive education. The problem formulation includes the principles of language use, the role of linguistic politeness, the ethics of interactive communication, and the importance of effective communication in creating an inclusive learning environment. By applying the principles of interactive communication, inclusive education can become more inclusive, equitable, and supportive of each student's development. The conclusion of this research indicates that interactive communication is the key to success in inclusive education, creating a friendly, supportive, and motivating learning environment for all students. Recommendations include the need to continuously apply the principles of interactive communication, raise awareness of the importance of linguistic politeness, and strengthen the relationships between all elements involved in the inclusive education process.